Effect of video tutorial delivery method on D/HH students’ content comprehension - Almalhy, Khalid M. (Frontiers in Psychology, 2022)
Using video tutorials to deliver instructional content has become common practices nowadays. However, it is required to investigate how to implement new methods to deliver instructional content to deaf students to ensure success of their learning and reduce their reliance on personnel support or consultation from hearing peers. Therefore, and in light of cognitive theory of multimedia learning, this study experimented three different video tutorial methods to deliver instructional content that are tailored to deaf students’ learning needs. The three methods included: (a) sign language only, (b) captioned text only, and (c) sign language and captioned text combined. The study applied a mixed methods research design using pretest-posttest quasi-experimental design (tests scores) and qualitative research design (interviews). Fifty-four undergraduate deaf students from a large university in Saudi Arabia participated in this study, and of those participants, fifteen deaf students participated in semistructured interviews. One-way analysis of variance results showed that using video tutorial that presents declarative content with captions only was significantly effective in comparison with the other methods. While the video tutorial that presents procedural content with sign language only was significantly effective in comparison with the other methods. Interview results confirmed the quantitative results. Practical and theoretical implications are discussed.